Mais Médicos Program in the context of changing strategies of medical training in the country: reflections and perspectives - Matias, Maria Claudia; Verdi, Marta; Finkler, Mirelle; Ros, Marco Aurelio Da (Saúde e Sociedade, 2019)
The professional training as a sustainability strategy of public health policy has to approach the needs of the Brazilian National Health System (SUS). Therefore, medical training has been the object of many governmental initiatives aimed at changing the training model. Recently, there has been a controversial and revealing debate of forces and interests that interfere in the problem about lack of vacancies and little training effectiveness regarding the SUS needs through the Mais Médicos Program (PMM) model. These forces condition the process of expansion and restructuring course of medical training and require a historical analysis and critical follow-up of the movements in progress, in the country. Thus, the reflections provided here aim to contribute to the PMM potentiation as an interference device in the field, and capable of adding new dimensions to the training process.